2019
DOI: 10.1088/1361-6668/ab4e7c
|View full text |Cite
|
Sign up to set email alerts
|

Giant enhancement of critical current density at high field in superconducting (Li,Fe)OHFeSe films by Mn doping

Abstract: Critical current density (Jc) is one of the major limiting factors for high field applications of iron-based superconductors.Here, we report that Mn-ions are successfully incorporated into nontoxic superconducting (Li,Fe)OHFeSe films.Remarkably, the Jc is significantly enhanced from 0.03 to 0.32 MA/cm 2 under 33 T, and the vortex pinning force density monotonically increases up to 106 GN/m 3 , which is the highest record so far among all iron-based superconductors. Our results demonstrate that Mn incorporation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 41 publications
1
14
1
Order By: Relevance
“…High-T c (42 K) FeSe-based compound (Li,Fe)OHFeSe [1] has received extensive attention because of the rich physics in the superconducting (SC) and normal states [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] as well as the potential for application. [19][20][21][22][23][24][25] The intercalated (Li,Fe)OHFeSe, sharing a similar electronic structure [7,8] with the prototypal FeSe monolayer, exhibits a strong electronic two-dimensionality and a nearly linear magnetic susceptibility extracted for the iron planes, [5] supporting the presence of magnetic fluctuations further evidenced by the inelastic neutron scatterings. [12,13] Recently, the Majorana zero bias mode [20] with quantized conductance plateau [21] is reported in the system.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…High-T c (42 K) FeSe-based compound (Li,Fe)OHFeSe [1] has received extensive attention because of the rich physics in the superconducting (SC) and normal states [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] as well as the potential for application. [19][20][21][22][23][24][25] The intercalated (Li,Fe)OHFeSe, sharing a similar electronic structure [7,8] with the prototypal FeSe monolayer, exhibits a strong electronic two-dimensionality and a nearly linear magnetic susceptibility extracted for the iron planes, [5] supporting the presence of magnetic fluctuations further evidenced by the inelastic neutron scatterings. [12,13] Recently, the Majorana zero bias mode [20] with quantized conductance plateau [21] is reported in the system.…”
Section: Introductionmentioning
confidence: 81%
“…On the other hand, the high-field critical current density (J c ) is observed to be remarkably enhanced by Mn doping. [24] So far most studies are focused on the physics related to the superconducting FeSe layers, with less attention paid on the intercalated (Li,Fe)OH layers. Previous results have shown that the Mn doping can affect the superconducting critical temperature (T c ) to certain extent in the (Li,Fe)OHFeSe single crystals.…”
Section: Introductionmentioning
confidence: 99%
“…This is detrimental to potential highfield applications of the high-Tc superconductivity. Fortunately, we have checked that the exotic intermediate vortex phase can be eliminated by introducing the transition metal Mn into the crystal structure, as done in our previous studies [31,47]: Doping Mn into (Li,Fe)OHFeSe films yields the common vortex phase diagram shown in figure 4(b). Meanwhile, the critical current density is strongly enhanced in the Mn-doped (Li,Fe)OHFeSe films compared to the undoped ones, and Tc can also be kept at a high value of 36.6 K [31].…”
mentioning
confidence: 96%
“…All samples were measured with the standard four-probe method. Part of the samples were patterned with a microbridge to determine Jc [31]. b.…”
mentioning
confidence: 99%
“…The self-field 𝐽c at 𝑇 = 2 K increases from 0.045 MA/cm −2 in FeSe to 1.9 MA/cm −2 in (Li,Fe)OHFeSe, indicating a high 𝐽c value achievable in high-𝑇c (Li,Fe)OHFeSe. [48,62] We note that, distinct from a monotonic 𝐽c variation of FeSe, 𝐽c of (Li,Fe)OHFeSe shows a local maximum 𝐽𝑐,max(𝐻, 𝑇 ) at a given 𝐻 and 𝑇 [see inset of Fig. S1(d)].…”
mentioning
confidence: 99%